Speaking Anxiety and Practice Opportunities in Relation to Students' Self-Confidence in Public Speaking - Nafizsha Donna Rienvillia; Sri Gustiani; Ahmad Khoirul Akhir Tanjung (Politeknik Negeri Sriwijaya, 2026)
ABSTRACT: This study explored students' experiences of speaking anxiety and practice opportunities in relation to their self-confidence in public speaking. The research employed a qualitative design involving ten students from the English Study Program of Politeknik Negeri Sriwijaya. Data were collected through semi-structured interviews and classroom observations and analyzed using thematic analysis proposed by Braun and Clarke (2006). The findings revealed that speaking anxiety negatively influenced students' self-confidence through fear of making mistakes, nervousness, fear of negative judgment, and anxiety experienced before, during, and after speaking activities. On the other hand, practice opportunities positively influenced students' confidence through frequent speaking practice, classroom speaking activities, lecturer support, and peer feedback. The study concludes that speaking anxiety tends to reduce students' confidence, whereas regular practice opportunities and supportive learning environments help students develop stronger self-confidence in public speaking. These findings provide useful implications for lecturers and educational institutions in creating effective public speaking learning environments Keywords: Public Speaking, Speaking Anxiety, Practice Opportunities, Self-Confidence, Qualitative Study